BOURDIEU'S CONCEPT OF REFLEXIVITY AS METALITERACY - Schirato, Tony; Webb, Jen (Cultural studies (London, England), 2003)
For Bourdieu, the extent to which agents can attain knowledge of, and negotiate, various cultural fields is dependent upon, and explicable in terms of, two epistemological types. The first is a practical sense (the 'logic of practice'), while the second involves a sort of conscious comprehension that he names 'reflexivity'. Bourdieu defines reflexivity as an interrogation of the three types of limitations (of social position, of field and of the scholastic point of view) that are constitutive of knowledge itself. But the reflexive relation to the habitus, the demands and influences exerted by cultural fields, and one's own practices within those fields, cannot be understood simply as something that is obtained by the subject; rather, any reflexive relation to the doxa and illusio of the field must be a constitutive part of that field. This paper identifies a number of principles taken from Bourdieu's work that clarify how, where and why the reflexive 'surpassing' of literacy might occur. But we also suggest, contra Bourdieu, that only fields that are informed or characterized by the scholastic point of view are likely to be characterized by the set of conditions constitutive of reflexive knowledge; and that the scholastic point of view is therefore, simultaneously, both a potential impediment to, and a condition (almost necessary) of the production of reflexive knowledge.